Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) = x^2 + 2x + 1 - x^2 +2x - 1 -3x^2 +x - x - 1
= - 3x^2 +4x -1
b) =5x^2 + 10x - 10x - 20 - 1/2 .(36 - 96x + 64x^2 ) +17
= 5x^2 - 20 - 18 - 48 x - 32x^2 +17
= -27x^2 - 48x - 3
Chúc bn hok tốt a !
\(5\left(x+2\right)\left(x-2\right)-\frac{1}{2}\left(6-8x\right)^2+17\)
\(=5\left(x^2-4\right)-\frac{1}{2}\left(36-96x+64x^2\right)+17\)
\(=5x^2-20+30-32x^2+17=-27x^2+27\)
a
(x+1)-(x-1)-3(x+1)(x-1)
=(x+1)-(x-1)-3x+1.(x-1)
=(x+1)-(x-1)-3x+x-1
=x+1-x+1-3x+x-1
=x-x-3x+x+1+1-1
=-2x
b,
5(x+2)(x-2)-1/2(6-8x)^2+17
=5x+10(x-2)-1/2(36-64x2)+17
=5x+10x-20-18+32x2+17
=5x+10x-20-18+17+32x2
=15x-21+32x2
a
(x+1)-(x-1)-3(x+1)(x-1)
=(x+1)-(x-1)-3x+1.(x-1)
=(x+1)-(x-1)-3x+x-1
=x+1-x+1-3x+x-1
=x-x-3x+x+1+1-1
=-2x
b,
5(x+2)(x-2)-1/2(6-8x)^2+17
=5x+10(x-2)-1/2(36-64x2)+17
=5x+10x-20-18+32x2+17
=5x+10x-20-18+17+32x2
=15x-21+32x2
b, 5(x + 2) (x - 2 ) - 1/2 (6-8x)2 + 17
=5x +10 (x - 2) - 1/2 . 6 - 1/2 . 8x +17
=5x + 10x - 20 - 3 - 4x +17
=15x - 17 -4x + 17
=15x - 4x -17 + 17
=11x - 0 =11x
a, (x+1)2 - (x-1)2 - 3(x+1) (x-1)
=(x+1)+(x-1).(x+1)-(x-1) - 3x+3x -3
=2x.0 - 3x
=-3x
1: =>3x+1=4
=>3x=3
hay x=1
2: \(\Leftrightarrow172\cdot x^2=\dfrac{1}{2^3}+\dfrac{7^9}{98^3}=\dfrac{1}{2^3}+\dfrac{7^9}{7^6\cdot2^3}\)
\(\Leftrightarrow172\cdot x^2=\dfrac{1}{2^3}+\dfrac{7^3}{2^3}=\dfrac{344}{2^3}\)
\(\Leftrightarrow x^2=\dfrac{1}{4}\)
=>x=1/2 hoặc x=-1/2
3: \(\Leftrightarrow\left[{}\begin{matrix}x-\dfrac{2}{9}=\dfrac{4}{9}\\x-\dfrac{2}{9}=-\dfrac{4}{9}\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{2}{3}\\x=-\dfrac{2}{9}\end{matrix}\right.\)
4: =>x+2=0 và y-1/10=0
=>x=-2 và y=1/10
\(A=\frac{\left(x^2+2x\right).\left(x-2\right)^2}{\left(x^3-4x\right).\left(x+1\right)}\)
\(A=\frac{\left(x^2+2x\right).\left(x^2-4x+4\right)}{\left(x^3-4x\right).\left(x+1\right)}=\frac{x^4-4x^3+4x^2+2x^3-8x^2+8x}{x^4+x^3-4x^2-4x}\)
\(A=\frac{x^4-2x^3-4x^2+8x}{x^4+x^3-4x^2-4x}=\frac{x^3.\left(x-2\right)-4x.\left(x-2\right)}{x^3.\left(x+1\right)-4x.\left(x+1\right)}=\frac{\left(x^3-4x\right).\left(x-2\right)}{\left(x^3-4x\right).\left(x+1\right)}=\frac{x-2}{x+1}\)
thay \(x=\frac{1}{2}\Rightarrow A=\frac{\frac{1}{2}-2}{\frac{1}{2}+1}=\frac{-\frac{3}{2}}{\frac{3}{2}}=-1\)
Vậy A=-1
5. (2 + x) (x+2) - \(\dfrac{1}{2}\) . (6-8x)2 + 17
= 5 ( x2 + 4x + 4) - \(\dfrac{1}{2}\). 4 ( 3 - 4x) 2+ 17
= 5x2 + 20 x + 20 - 2 ( 9 - 24x + 16x2) + 17
= 5x2 + 20x + 20 - 18 + 58x - 32x2 + 17
= -27x2 + 78 x + 19